The Impact of Industrial Training on Students’ Academic Performance - Obasi, Rosemary (Advances in Social Sciences Research Journal, 2015)
We studied the impact of IT on students’ performance, using Benson Idahosa University as a case study. To achieve this purpose, performance was measured using six different variants of performance while seven independent variables were measured and used to test the hypotheses. A total of fifty-three students were sampled. Questionnaire was used to elicit data for the study. The data collected were analyzed using descriptive statistics and correlation analysis and hypotheses tested using t-test statistics and regression. Among the 6 items on Performance issues, 4 produced statistically significant in respondents’ ratings. We find that, Stipends, Number of Units, IT Relevance, use of Tools, and supportive Boss impact on students’ performance. Supportive Boss is a key variable that ensures that IT impact on students’ academic performance since; it cuts across all of the variants of performance. We conclude that, industrial training impact on student’s performance. We therefore recommend that institutions should include IT training in their accounting program and institutions should endeavour to collect relevant data base from their IT students.